Wolbachia effects on Rift Valley fever virus infection in Culex tarsalis mosquitoes. - Brittany L Dodson; Elizabeth S Andrews; Michael J Turell; Jason L Rasgon (Public Library of Science (PLoS), 2017)
Innovative tools are needed to alleviate the burden of mosquito-borne diseases, and strategies that target the pathogen are being considered. A possible tactic is the use of Wolbachia, a maternally inherited, endosymbiotic bacterium that can (but does not always) suppress diverse pathogens when introduced to naive mosquito species. We investigated effects of somatic Wolbachia (strain wAlbB) infection on Rift Valley fever virus (RVFV) in Culex tarsalis mosquitoes. When compared to Wolbachia-uninfected mosquitoes, there was no significant effect of Wolbachia infection on RVFV infection, dissemination, or transmission frequencies, nor on viral body or saliva titers. Within Wolbachia-infected mosquitoes, there was a modest negative correlation between RVFV body titers and Wolbachia density, suggesting that Wolbachia may slightly suppress RVFV in a density-dependent manner in this mosquito species. These results are contrary to previous work in the same mosquito species, showing Wolbachia-induced enhancement of West Nile virus infection rates. Taken together, these results highlight the importance of exploring the breadth of pathogen modulations induced by Wolbachia.